Expression and secretion of glucanase in conjunction with pectinase in a recombinant yeast - Van Rensburg, Pierre,1968- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.